Sistem Informasi Usaha Mikro Kecil Dan Menengah Di Kelurahan Buaran Berbasis Web - Muchlis Fadhilah Akbar; Yudi Kurniawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Small and medium enterprises (SME) are now one of the pillars of the Indonesian economy, the crisis that occurred in 1998 provided a very valuable lesson to the Indonesian people how SME saved the country's economy. Therefore, it is necessary to have a platform specifically developed to support the growth and development of these SME. By raising examples of SME problems in Buaran Village related to the lack of product promotion efforts and data collection which is still constrained by the difficulty of business actors who still have to come directly to register their businesses, an information system is developed as a medium for SME. This SME information system can be designed on a web-based basis, using the PHP programming language and the Laravel framework and using the prototype method. With the existence of this SME information system, it can help SME owners and the Buaran Village to promote and collect data on SME around their area.